The Effect of Immersion in Soda Containing Sucrose and Aspartame on The Compressive Strength of Bulk-fill Composite Resin - Christiawan, Kevin Anthony; Ratnasari, Dina (Indonesian Dental Association, 2022)
Introduction: Soda is a popular drink and contains sucrose as natural sweetener, and aspartame as artificial sweetener, both of which have acidic properties that affect the restorative material. Bulk-fill composite resin is a type of composite resin that can be polymerized with a thickness of 4-5 mm as well as better physical and mechanical properties for chewing forces. Objective: To determine the effect of immersion in soda containing sucrose and aspartame on the compressive strength of bulk-fill composite resins. Methods: This study used 30 samples of bulk-fill composite resin in the form of a cylinder with a diameter of 4 mm and a height of 6 mm, divided into 3 groups. Group A was immersed in artificial saliva for 24 hours. Group B was immersed in soda containing sucrose for 6 hours and in artificial saliva for 18 hours. Group C was immersed in soda containing aspartame for 6 hours and in artificial saliva for 18 hours. The samples were immersed for 6 days in an incubator at 37°C. The compressive strength was measured and calculated using the Universal Testing Machine (UTM). Results: The result of compressive strength on artificial salive immersion was 318,65 ± 30,23, on soda containing sucrose immersion was 312,59 ± 33,10, on soda containing aspartame immersion was 316,80 ± 23,49. One-Way ANOVA test showed that the compressive strength value of bulk-fill composite resin was not significantly different among groups (p > 0.05). Conclusion: The effect of immersion in soda containing sucrose and aspartame showed no difference on the compressive strength of bulk-fill composite resins. ABSTRAK Pendahuluan: Minuman soda merupakan minuman yang populer dan mengandung pemanis alami yaitu sukrosa dan pemanis buatan yaitu aspartam, keduanya memiliki sifat asam yang berpengaruh terhadap bahan restorasi. Resin komposit bulk-fill merupakan jenis resin komposit yang dapat dipolimerisasi dengan ketebalan 4-5 mm serta memiliki sifat fisik dan mekanik yang lebih baik untuk kekuatan kunyah. Tujuan: Untuk mengetahui pengaruh perendaman minuman soda mengandung sukrosa dan aspartam terhadap kekuatan tekan resin komposit bulk-fill. Metode: Penelitian ini menggunakan sampel resin komposit bulk-fill berbentuk silinder dengan diameter 4 mm dan tinggi 6 mm sebanyak 30 sampel, sampel dibagi menjadi 3 kelompok. Kelompok A yang direndam dalam saliva buatan selama 24 jam, kelompok B yang direndam dalam soda mengandung sukrosa selama 6 jam dan 18 jam dalam saliva buatan, dan kelompok C yang direndam dalam soda mengandung aspartam 6 jam dan 18 jam dalam saliva buatan. Perendaman sampel dilakukan selama 6 hari dalam inkubator 37°C. Kekuatan tekan diuji dan dihitung menggunakan Universal Testing Machine (UTM). Hasil: Hasil kekuatan tekan pada saliva buatan 318,65 ± 30,23, pada soda mengandung sukrosa 312,59 ± 33,10, pada soda mengandung aspartam 316,80 ± 23,49. Uji dengan One-Way ANOVA menunjukkan nilai compressive strength resin komposit bulk-fill tidak berbeda signifikan antar tiap kelompok (p > 0,05). Kesimpulan: Tidak terdapat perbedaan pengaruh perendaman minuman soda mengandung sukrosa dan aspartam terhadap kekuatan tekan resin komposit bulk-fill.